The Turning Point: o gênero discursivo videoanimação sob a perspectiva dialógica bakhtiniana - Castro, Kleissiely de (Universidade Federal de São Carlos, 2025)
Video animations have become the object of study for researchers interested in investigating their educational, semiotic and discursive potential (Ferreira; Dias; Villarta-Neder, 2019; Vieira, 2008; Ferreira; Almeida, 2018; Barbosa Júnior, 2019; Dias, 2022; Silva; Ferreira, 2024). As part of this research, this work aims to analyze the video animation The Turning Point (2020), by Steve Cutts, from a Bakhtinian dialogic perspective, based on the constitutive elements of the utterance (Bakhtin, 2016), and the verb-visual relationship (Brait, 2009, 2013, 2022). To this end, we assume that video animation is a discursive genre, since it is a concrete utterance that is defined in specific communication conditions. The selection of the video animation is justified by its provocative and reflective approach to contemporary environmental and social crises and their ethical and moral consequences. The basic theoretical methodological foundation is the dialogical perspective, derived from Bakhtin and the Circle (Volóchinov, 2017; Bakhtin, 2016, 2017a, 2017b). Through it, we investigate how the discursive genre video animation mobilizes the verb-visual relationship to reflect and refract aspects of reality. We argue that verbo-visuality should not be understood as an arbitrary combination of the verbal and the visual, but rather a semiotic, discursive and ideological project that involves the interlocutor in an active and responsive process of constituting meanings. We believe that investigating the complexity of contemporary utterances, marked by the verb-visual relationship, allows for a deeper understanding of how human interaction takes place in the context of digital media. Thus, we find that analyzing this genre through a dialogical lens allows us to read and interpret it as a statement that transcends the realm of entertainment and establishes itself as a means of critical intervention in society. We understand that the verbal-visual condition of language not only expands the expressive possibilities of the statement, but also reflects an ethical commitment to contemporary issues, since it acts at the intersection between language, ideology, and aesthetics. The analysis of The Turning Point allowed us to understand that the articulation between the verbal and imagery dimensions enhances the process of meaning constitution, since it goes beyond verbal materiality and demands a responsive stance from the reader. Given this, we hope that this research will contribute to discussions that highlight those utterances, manifested in their typical forms, should be considered in their unique realization in the event of life.
The Turning Point: the discursive genre of video animation from a Bakhtinian dialogical perspective
Keywords: The Turning Point; Gêneros discursivos; Enunciado; Verbo-visualidade; Videoanimação; Discursive genres; Utterance; Verbo-visuality; Video animation; LINGUISTICA, LETRAS E ARTES::LINGUISTICA